Sarcomas of the lower female genital tract (vulva, vagina, and cervix): literature review and own cases - K. V. Safronova; A. S. Artemyeva; A. O. Nyuganen; A. A. Sidoruk; O. A. Smirnova; N. A. Mikaya; I. V. Berlev; A. F. Urmancheeva; E. A. Ulrikh (Опухоли женской репродуктивной системы)
The article covers different aspects of clinical manifestations, diagnosis, and treatment of vulvar, vaginal, and cervical sarcomas.